Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a/ S = ( - 2/3 + 1) - (7/5 - 0,2) + )7/15 - 1 + 4/3) = - 2/3 + 1 - 7/5 + 1/5 +7/15 - 1 + 4/3 = 2/3 - 6/5 + 7/15 = 10/15 - 18/15 + 7/15 = - 1/15.
b/ S = 0,25 - 9- (- 3/4) - [ - 7/3 + (-9/2)] - 5/6 = 1/4 - 9 + 3/4 + 7/3 + 9/2 - 5/6 = - 8 + 14/6 + 27/6 - 5/6 = - 8 + 6 = - 2
\(=(\frac{3}{4}-\frac{1}{4})-\frac{7}{3}+\frac{9}{2}-\frac{5}{6}=\frac{1}{2}+\frac{9}{2}-\frac{14}{6}-\frac{5}{6}=5-\frac{19}{6}=\frac{11}{6}\)
Kết bạn nha bạn
Bài làm
\(\frac{3}{4}-0,25-\left(\frac{7}{3}+\frac{-9}{2}\right)-\frac{5}{6}\)
\(=\frac{3}{4}-\frac{1}{4}-\left(\frac{14}{6}+\frac{-27}{6}\right)-\frac{5}{6}\)
\(=\frac{1}{2}+\frac{13}{6}-\frac{5}{6}\)
\(=\frac{3}{6}+\frac{13}{6}-\frac{5}{6}\)
\(=\frac{11}{6}\)
# Học tốt #
\(=\)\(\frac{1}{2}\)-\(\frac{-13}{6}\)-\(\frac{5}{6}\)
\(=\)\(\frac{3}{6}\)-\(\frac{-13}{6}\)-\(\frac{5}{6}\)
\(=\)\(\frac{11}{6}\)
\(\frac{3}{4}-0,25-\left(\frac{7}{3}+\frac{-9}{2}\right)-\frac{5}{6}\)
\(=\frac{3}{4}-\frac{1}{4}-\left(\frac{14}{6}+\frac{-27}{6}\right)-\frac{5}{6}\)
\(=\frac{1}{2}-\frac{-13}{6}-\frac{5}{6}\)
\(=\frac{3}{6}+\frac{13}{6}-\frac{5}{6}\)
\(=\frac{16}{6}-\frac{5}{6}\)
\(=\frac{11}{6}\)
1)
a. \(\left(3x^2-50\right)^2=5^4\)
\(\Leftrightarrow3x^4-50=625\)
\(\Leftrightarrow3x^4=675\)
\(\Leftrightarrow x^4=225\)
\(\Leftrightarrow x=\sqrt{15}\)
2)
a. \(\frac{\left(3^4-3^3\right)^4}{27^3}=\frac{3^{16}-3^{12}}{\left(3^3\right)^3}=\frac{3^{12}.3^4-3^{12}}{3^9}=\frac{3^{12}\left(3^4-1\right)}{3^9}\)
\(=\frac{3^{12}.80}{3^9}=3^3.80=27.80=2160\)
b. \(\frac{25^3}{\left(5^5-5^3\right)^2}=\frac{\left(5^2\right)^3}{5^{10}-5^6}=\frac{5^6}{5^6.5^4-5^6}=\frac{5^6}{5^6\left(5^4-1\right)}\)
\(=\frac{5^6}{5^6.624}=\frac{1}{624}\)
\(S=\frac{3}{4}-0,25\left[\frac{7}{3}+\left(-\frac{9}{2}\right)\right]-\frac{5}{6}\)
\(\Rightarrow S=\frac{3}{4}-0,25.\frac{13}{6}-\frac{5}{6}\)
\(\Rightarrow S=\frac{3}{4}-\frac{1}{4}.\frac{13}{6}-\frac{5}{6}\)
\(\Rightarrow S=\frac{18}{24}-\frac{13}{24}-\frac{20}{24}\)
\(\Rightarrow S=\frac{18-13-20}{24}=\frac{-15}{24}\)
`3/4-0,25-(7/3-9/2)-5`
`=3/4-1/4-7/3+9/2-5`
`=1/2-7/3+9/2-5`
`=(1/2+9/2)-7/3-5`
`=5-7/3-5`
`=(5-5)-7/3`
`=-7/3`
\(\dfrac{3}{4}\) \(-\) \(0,25\) \(-\) \(\left(\dfrac{7}{3}-\dfrac{9}{2}\right)\) \(-\) \(5\)
\(=\dfrac{3}{4}-\dfrac{1}{4}-\left(-\dfrac{13}{6}\right)-5\)
\(=\dfrac{2}{4}+\dfrac{13}{6}-5\)
\(=\dfrac{8}{3}-5\)
\(=\dfrac{-7}{3}\)